Three-Directional Reconstruction of a Massive Perineal Defect after Wide Local Excision of Extramammary Paget's Disease - Cho, Seung Woo; Chang, Hak; Kwon, Sung Tack (Archives of Plastic Surgery, 2016)
Extramammary Paget's disease (EMPD) is a rare, slow-growing intraepithelial malignancy that mainly involves the genital region, including the vulva, penis, scrotum, perianal, and periurethral areas. Although several treatment options exist, wide local excision with a safe margin is considered the treatment of choice. After resection of the lesion, it is often challenging to reconstruct the defect because defects in the perineal region require adequate volume for protection and are susceptible to infections, which is a particularly significant risk for large defects. We report a case of perivulvar EMPD that was reconstructed with three-directional local flaps after wide excision of the tumor. We covered the defect sequentially using the following 3 flaps: a gracilis myocutaneous flap from the left thigh, a bipedicled V-Y advancement flap from the lower abdomen, and an internal pudendal artery perforator-based island flap from the right buttock. To the best of our knowledge, this report is the first to describe a three-directional approach to extensive perivulvar reconstruction.
Keywords: Myocutaneous flaps; Perforator flaps; Vulva